Scientific Information: A Partnership between the Library and the Academic Community - Dekeyser, Raf (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
Libraries are sometimes erroneously considered to be rather passive recipients for the conservation of literary and scientific production. Such a picture was never correct, since there has always been a strong relation between the libraries and the centres of book production. Such a relation is even more strongly present today in our modern universities and other centres of research. Our budget is always too limited to allow anything but an acquisition policy that is tailored as much as possible to the specific needs of our customers. In the library lies the beginning of every research project, since it contains the necessary sources of information; the library forms also the ultimate goal of a research project, since this is the place where the publications that consolidate its results should be deposited. The activities of a research institute and its supporting library are so strongly intertwined that a librarian cannot afford to remain ignorant about the mechanisms through which scientific and scholarly information are established.